Antenatal micronutrient supplementation and third trimester cortisol and erythropoietin concentrations. Issue 1 (24th July 2014) - Christian, Parul; Nanayakkara‐Bind, Ashika; Schulze, Kerry; Wu, Lee; LeClerq, Steven C.; Khatry, Subarna K.
Abstract: Antenatal iron and multiple micronutrient supplementation has been shown in randomized trials to improve birthweight, although mechanisms are unknown. We examined late pregnancy serum erythropoietin (EPO) and cortisol concentrations in relation to maternal micronutrient supplementation and iron status indicators (haemoglobin, serum ferritin, soluble transferrin receptor) in 737 rural Nepalese women to explore evidence of stress or anaemia‐associated hypoxia. A double‐masked randomized control trial was conducted from December 1998 to April 2001 in Sarlahi, Nepal, in which women received vitamin A alone (as control), or with folic acid (FA), FA + iron, FA + iron + zinc and a multiple micronutrient supplement. In a substudy, we collected maternal blood in the first and third trimester for biochemical assessments. Generalized estimating equations linear regression analysis was used to examine treatment group differences. EPO was ∼14–17 mIU mL −1 lower ( P  < 0.0001) in late pregnancy in groups receiving iron vs. the control group, with no difference in the FA‐only group. Cortisol was 1.3  μ g dL −1 lower ( P  = 0.04) only in the micronutrient supplement group compared with the control group. EPO was most strongly associated with iron status indicators in groups that did not receive iron, and in the non‐iron groups cortisol was positively correlated with EPO ( r  = 0.15, P  < 0.01) and soluble transferrin receptor (sTfR, r  = 0.19, P  < 0.001). In adjusted analyses, third trimester EPO was associated with a reduction in low birthweight, whereas cortisol was negatively associated with length of gestation and higher risk of preterm birth. Iron and multiple micronutrient supplementation may enhance birth outcomes by reducing mediators of maternal stress and impaired erythropoiesis.